Kriteriji za prepoznavanje sovražnega govora v jeziku - Campos Ferreira, Raphael (Teorija in praksa, 2012)
A text by "Tomaž Majer" stimulated a debate on hate speech among professionals and the public in general. Due to the need for categorisation to identify the elements of hate speech in texts and discourse, we rely on the existing literature about this subject to identify and separate hate speech from defamation so that we can establish new criteria for identifying hate speech in language
Keywords: Hate speech; Sovražni govor; Spletni portali; Web portals; Internet; Freedom of speech; Digital media; Svoboda govora; Elektronski mediji; Case study; Slovenia; Študija primera; Slovenija